Energy substrates that fuel fast neuronal network oscillations - Galow, Lukas; Schneider, Justus; Lewen, Andrea; Ta, Thuy-Truc; Papageorgiou, Ismini E.; Kann, Oliver (Frontiers in neuroscience, 2014)
Fast neuronal network oscillations in the gamma-frequency band (30-100 Hz) provide a fundamental mechanism of complex neuronal information processing in the hippocampus and neocortex of mammals. Gamma oscillations have been implicated in higher brain functions such as sensory perception, motor activity and memory formation. The oscillations emerge from precise synapse interactions between excitatory principal neurons such as pyramidal cells and inhibitory GABAergic interneurons, and they are associated with high energy expenditure. However, both energy substrates and metabolic pathways that are capable to power cortical gamma oscillations have been less defined. Here, we investigated the energy sources fueling persistent gamma oscillations in the CA3 subfield of organotypic hippocampal slice cultures of the rat.
Gesehen am 14.10.2020